Pharmacokinetics, safety, and bioequivalence of apixaban tablets in healthy Chinese subjects under fasting and fed conditions - Luo, Hong-Yu; Yao, Zhen-Jiang; Long, Hui-Zhi; Zhou, Zi-Wei; Xu, Shuo-Guo; Li, Feng-Jiao; Cheng, Yan; Wen, Dan-Dan; Deng, Ping; Guan, Yue-Qing; Gao, Li-Chen (International journal of clinical pharmacology and therapeutics, 2023)
To evaluate the pharmacokinetics (PK), safety, and bioequivalence of two formulations of apixaban in healthy Chinese subjects under fasting and fed conditions. A single-center, randomized, open, single-dose, two-period crossover PK study was carried out under fasting and fed conditions in 64 healthy subjects enrolled in either the fasting (36 subjects) or the fed (28 subjects) arms of the study. Subjects received a single oral dose of 2.5 mg apixaban tablets as test (T) or reference (R) formulation. The primary PK parameters determined were the area under the plasma concentration-time curve from zero to t and ∞ (AUC and AUC ) and the maximal plasma concentration (C ). Safety was assessed mainly from the occurrence of adverse events (AEs). A single drop-out in the fed arm of the trial was excluded from the statistical evaluation. The 90% confidence intervals (CIs) for the geometric mean ratio (GMR) for T/R using AUC were 95.4 - 100.9% and 97.8 - 103.8%, and for AUC were 95.3 - 100.6% and 98.3 - 104.3% under fasting (36 subjects) and fed (27 subjects) conditions, respectively. Similarly, the 90% CIs for C were 94.6 - 103.1% and 88.8 - 102.0% under fasting (36 subjects) and the fed (27 subjects) conditions, respectively. Therefore, the 90% CIs for the T/R AUC and C ratios were within the standard range for bioequivalence (80.0 - 125.0%). There were no serious adverse events (SAEs). The test and reference 2.5 mg apixaban tablets were bioequivalent and both showed good tolerability and safety.